Modern Problems of Pedagogical Education - A. V. Lubkov (Образование и наука)
Introduction. Nowadays, the fate of any state depends increasingly on the well-being and dynamic development of the national education system. The post-industrial era has generated and continues to generate numerous challenges to this crucial social institution, including teacher training. The questions related to teacher qualities and what a teacher should be like today and in the near future is relevant both on a global scale and on the borders of a certain country, and Russia in particular.The aim of the article is to discuss the content and essential factors of a current modernisation process of pedagogical education at the current stage and to propose specific measures, which contribute to the formation of the system of continuing vocational training of teaching personnel.Methodology and research methods. The methodological framework of the research is based on: current theoretical models and modernisation conceptions; the key provisions of problem-based axiological, hermeneutical and anthropological approaches; the methods of structural-functional and comparative analysis.Results and scientific novelty. Modernisation of education is considered from the perspective of relationships and synthesis of institutional structures, sociocultural context, and axiological foundations of changes and individual-personal component, which determine the vector of progressive evolution of society. To study a complex and nonlinear process of social innovation, the author believes that it is necessary to appeal to metaphysical aspects of human personality, its national, civil and civilisational identity, which is a special resource of development. The author’s understanding of innovation, where a person is a carrier of value, purpose, volitional and intellectual principles, allows the straightforward and mechanistic understanding of laws of social development in general and the laws of education and pedagogy to be overcome and the reduction of norms and values due to overloads of information flows and many other factors to be counteracted. Since any person is a social actor, the main indicator of progressiveness or reactivity of changes, the key role in the modernisation process belongs to the personal factor, in the educational process – the teacher’s identity. Therefore, the most important strategic task is the fundamental methodological and content-based training of the teacher, whose work will contribute to the future of society and the state.The research undertaken and the author’s conclusions expand the discourse on the national system of continuing pedagogical education. It is highlighted that the professionalism of the Russian teacher should be based on the civilisation heritage of the country and its people, and the model of social transformations and the coordinated image of the future should correspond to the traditional Russian ideas of collegiality, justice and human solidarity.Practical significance. The research materials can be used in the practice of specialists, who are responsible for the development of the system of continuing pedagogical education, when forming a policy in this area. The results of the study are of practical importance for lecturers of pedagogical universities, school teachers, students and all those who are interested in the perspectives of Russian education.